2015
DOI: 10.1016/j.quageo.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Protein diagenesis in Patella shells: Implications for amino acid racemisation dating

Abstract: The inter-and intra-crystalline fractions of Patella vulgata limpets recovered from archaeological sites in Northern Spain (covering Neolithic, Mesolithic, Magdalenian, Solutrean, and Aurignacian periods) were examined for amino acid composition and racemisation over time. The calcitic apex and rim areas of the shells were found to probably be composed of similar proteins, as the D/L values and amino acids were comparable and varied in the same way with increasing age; however, the mineral structures present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 47 publications
0
19
0
4
Order By: Relevance
“…The shell consists almost entirely of calcium carbonate, with a small percentage of organic material and water. The microscopic structure is very complex and varies with species (Ortiz et al, 2015). Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The shell consists almost entirely of calcium carbonate, with a small percentage of organic material and water. The microscopic structure is very complex and varies with species (Ortiz et al, 2015). Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Each layer has a different structure -some layers are made from calcite and some from aragonite, and the orientation and arrangement varies from layer to layer including prismatic and lamellar arrangements of crystal units. The basic structure of M-layers is known as the first-order structure, with second and third orders being identified at finer scales (see for example Ortiz et al, 2015;Szabó and Koppel, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Demarchi et al (2013) reported similar THAA abundance patterns in Patella vulgata, with Asp, Glu and Ala being the most abundant and geochronologically useful amino acids, although Asp is less abundant in these taxa than reported from P. vulgata. Change in the relative concentration can be an indication of closedsystem behaviour or remnant protein structure (Penkman et al, 2008;Demarchi et al, 2013;Ortiz et al, 2015). The relatively narrow confidence intervals on the relative amino acid abundance plot indicate consistency across the amino acids.…”
Section: Total Hydrosoluble Amino Acid Compositionmentioning
confidence: 99%
“…Longer hydrolysis times generally increase D/L values (Canoira et al, 2003), with the difference typically proportionally greater in younger samples, and for amino acids with the higher racemization rates, such as Asp. The influence of pre-treating with bleach to isolate the intra-crystalline fraction is less predictable, with some studies reporting an increase in D/L values (e.g., for Glycymeris, Demarchi et al, 2015; ostrich eggshell, Crisp et al, 2013), others a decrease (e.g., for Patella, Ortiz et al, 2015), and others no effect (e.g., for ostracodes, Bright and Kaufman, 2011).…”
Section: Other Factors Influencing the Comparison Of A/i And D/l Valuesmentioning
confidence: 99%